2010
DOI: 10.1262/jrd.09-097a
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Length of Cell Cycles, Cleavage Pattern and Developmental Competence in Bovine Embryos Generated by <i>In Vitro</i> Fertilization or Parthenogenesis

Abstract: Abstract. This study was conducted to study the kinetics of initial cell divisions in relation with the cleavage patterns in viable (with the ability to develop to the blastocyst stage) and non-viable bovine embryos and parthenotes. The kinetics of in vitro development and cleavage patterns were observed by time lapse cinematography. The length of the first and second but not third cell cycle differed significantly between the viable and non-viable embryos after IVF or parthenogenesis. Viable embryos had signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
91
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 43 publications
10
91
2
Order By: Relevance
“…Similar results were obtained by another group who observed rates of 40% (cleavage up to 30 h post-IVF) and 10% (cleavage 30-36 h post-IVF, HUMBLOT et al, 2005), which are in agreement with previous reports (ISOM et al, 2012;LECHNJAK et al, 2008;SOMFAI et al, 2010) and later studies in which late-cleaving embryos resulted in lower blastocyst and pregnancy rates (BASTOS et al, 2008;MAGLI et al, 2007;SUGIMURA et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were obtained by another group who observed rates of 40% (cleavage up to 30 h post-IVF) and 10% (cleavage 30-36 h post-IVF, HUMBLOT et al, 2005), which are in agreement with previous reports (ISOM et al, 2012;LECHNJAK et al, 2008;SOMFAI et al, 2010) and later studies in which late-cleaving embryos resulted in lower blastocyst and pregnancy rates (BASTOS et al, 2008;MAGLI et al, 2007;SUGIMURA et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…In the same report, it was also reported that blastocysts derived from 3-or 4-and 5-to 8-cell embryos had a lower incidence of chromosomal abnormalities. On the other hand, an abnormal cleavage pattern may occur during the first embryonic cleavage, resulting in embryos with 3 or 4 blastomeres and abnormal chromosome numbers [22,23]. Selection of embryos with large blastomere numbers at an early developmental stage may therefore lead to contraselection of embryos with impaired developmental competence.…”
mentioning
confidence: 99%
“…This result is different from previous observations in cattle embryos, in which the length of the second embryonic cell cycle was found to correlate with the developmental competence to the blastocyst stage [36]. Our data suggest clearly that, for early selection of high quality IVP embryos, careful investigation should be made for subsequent cleavages after the 2-cell stage.During embryo culture, an abnormal cleavage pattern may occur at the first embryonic cell division, resulting in embryos with unusually high numbers of blastomeres and abnormal chromosome numbers [22,23]. Abnormal cleavage pattern is believed to have a great influence on development of IVP porcine embryos [37]; however, it has not been studied substantially in this species yet.…”
mentioning
confidence: 99%
“…Most aspirated oocytes are at the stage of metaphase II and develop two pronuclei after ICSI; yet, we surmise that in some, the cascade responsible for the activation of mitosis is disturbed. It ought to be mentioned that bovine zygotes that underwent direct division from one to three cells had developmental ability comparable to embryos with normal division, but with a high rate of chromosomal abnormalities [8].…”
Section: Resultsmentioning
confidence: 99%